5G-Advanced: network-controlled repeater - Nan ZHANG; Ziyang LI; Ruyue LI; Wei CAO (Dianxin kexue)
Radio frequency (RF) repeaters have been deployed in 2G, 3G and 4G to improve the coverage of cellular system.While it is treated as a cost effective solution to extend the network coverage, conventional RF repeaters simply perform amplify-and-forward operation based on the set-up without the capability of doing flexible adjustments based on control and scheduling indication from network.An overview on the new study item in 5G-Advanced was given, i.e.network-controlled repeater.As an enhancement over conventional RF repeaters, network-contrdled repeater will enable the repeater to receive and process repeater control information from the network and perform its amplify-and-forward operation in a more efficient manner including the directive forwarding of the signal, dynamic on-/off of transmissions and receptions, and simplified network integration.